Outcome and predictive factors in uterine carcinosarcoma using postoperative radiotherapy: a Rare Cancer Network study - (:unkn) unknown (PAGEPRESS PUBL, 2016)
Uterine carcinosarcomas (UCS) are rare tumors. Consensus regarding therapeutic management in non-metastatic disease is lacking. This study reports on outcome and predictive factors when using postoperative radiotherapy. We analyzed a retrospective analysis in 124 women treated between 19872007 in the framework of the Rare-Cancer-Network. Median follow-up was 27 months. Postoperative pelvic EBRT was administered in 105 women (85%) and 92 patients (74%) received exclusive or additional vaginal brachytherapy. Five-year overall survival (OS), disease-free survival (DFS), cancer specific survival (CSS) and locoregional control (LRC) were 51.6% (95% CI 35-73%), 53.7% (39-71%), 58.6% (38-74%) and 48% (38-67%). Multivariate analysis showed that external beam radiation therapy (EBRT) >50Gy was an independent prognostic factor for better OS (P=0.03), CSS (P=0.02) and LRC (P=0.01). Relative risks (RR) for better OS (P=0.02), DFS (P=0.04) and LRC (P=0.01) were significantly associated with younger age (<= 60 years). Higher brachytherapy (BT)-dose (>9Gy) improved DFS (P=0.04) and LRC (P=0.008). We concluded that UCS has high systemic failure rate. Local relapse was reduced by a relative risk factor of over three in all stages of diseases when using higher doses for EBRT and brachytherapy. Postoperative RT was most effective in UCS stage I/II-diseases.
Keywords: Carcinosarcoma; uterine malignancies; radiotherapy; brachytherapy; toxicity; MIXED MULLERIAN TUMORS; RADIATION-THERAPY; PROGNOSTIC-FACTORS; VAGINAL BRACHYTHERAPY; PELVIC RADIOTHERAPY; ENDOMETRIAL CANCER; EARLY-STAGE; SARCOMAS; UTERUS; TRIAL